텍스트 마이닝에서 심층 신경망을 이용한 문서 분류 - 이보희; Bo-hui Lee; 이수진; Su-jin Lee; 최용석; Yong-seok Choi (Ŭngyong tʻonggye yŏnʼgu, 2020)
문서-용어 빈도행렬은 그룹정보가 존재하는 문서들의 용어를 추출한 것으로 일반적인 텍스트 마이닝에서의 자료이다. 본 연구에서는 연구 분야 성격에 따른 문서 분류를 위해 문서-용어 빈도행렬을 생성하고, 전통적인 용어 가중치함수인 TF-IDF와 최근 잘 알려진 용어 가중치 함수인 TF-IGM을 적용하였다. 또 용어 가중치가 적용된 문서-용어 가중행렬에 문서분류 정확도 향상을 위해 핵심어를 추출하여 문서-핵심어 가중행렬을 생성하였다. 핵심어가 추출된 행렬을 바탕으로, 심층 신경망을 이용해 문서를 분류하였다. 심층 신경망에서 최적의 모델을 찾기 위해 매개변수인 은닉층과 은닉노드수를 변화해가며 문서 분류 정확도를 확인하였다. 그 결과 8개의 은닉층을 가진 심층 신경망 모델이 가장 높은 정확도를 보였으며 매개변수 변화에 따른 모든 TF-IGM 문서 분류 정확도가 TF-IDF 문서 분류 정확도보다 높은 것을 확인하였다. 또한 개별 범주에 대한 문서 분류 분석 결과를 서포트 벡터 머신과 비교했을 때 심층신경망이 대부분의 결과에서 더 좋은 정확도를 보임을 확인하였다. The document-term frequency matrix is a term extracted from documents in which the group information exists in text mining. In this study, we generated the document-term frequency matrix for document classifi-cation according to research field. We applied the traditional term weighting function term frequency-inverse document frequency (TF-IDF) to the generated document-term frequency matrix. In addition, we applied term frequency-inverse gravity moment (TF-IGM). We also generated a document-keyword weighted matrix by extracting keywords to improve the document classification accuracy. Based on the keywords matrix extracted, we classify documents using a deep neural network. In order to find the optimal model in the deep neural network, the accuracy of document classification was verified by changing the number of hidden layers and hidden nodes. Consequently, the model with eight hidden layers showed the highest accuracy and all TF-IGM document classification accuracy (according to parameter changes) were higher than TF-IDF. In addition, the deep neural network was confirmed to have better accuracy than the support vector machine. Therefore, we propose a method to apply TF-IGM and a deep neural network in the document classification.